The role of organization-level factors on informal learning process - Talukder, Sazzad Hossain (My University, 2016)
This study discusses the nature of informal learning process in business organizations, and the importance of different organization-level factors in this process. The purpose of this study is to understand the role of organization-level factors on informal learning process with three subquestions: how informal learning process takes place in business organizations, what organization-level factors affects informal learning process, and how informal learning process is affected by organizational-level factors. The theoretical background of this study includes literatures on the concept of informal learning, its process, and organization-level factors that can affect informal learning process. The empirical research has been conducted in this study by face-to-face interviews. The interviews were conducted between June and August 2015 in Dhaka, Bangladesh. Thirteen interviews were made with the employees from different hierarchical levels from four freight forwarding MNCs in Bangladesh. Constant comparative analysis has been used to process the collected data until reaching a level of saturation. The empirical research found that all the phases in an informal learning process are not linear and sequential, and the role of organization-level factors on each phase varies with the degree and nature of each factor. In addition, the results also revealed that all the organization-level factors do not interact with each other while playing their role on informal learning process. The ﬁndings of this study considerably extend our understanding of the important role of HRD, manager, colleague, culture, and work structure on informal learning process in the workplace. However, future research in different organizational contexts is required to generalize the findings of this study.